APLIKASI TEKNOLOGI PENDIDIKAN BAGI GURU DAN DOSEN - Suprayekti Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Educational technology as a discipline can be explained by theory and practice. Educational technology as a theory based with empiric evidence as result of research. Educational technology as a practice is a recipe use as an alternative solution for students learning problems Teacher can apply learning recipe to optimize students learning result. This application used to help professional competence regarding the Undang-Undang Guru dan Dosen No. 14 Tahun 2005. Some of the applications are students’ analysis, learning process and grading.